Pengaruh Kualitas Pelayanan, Harga Dan Promosi Terhadap Kepuasan Konsumen di Muliamart - Garnis Savitri; Nersiwad Nersiwad; Budi Utami (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The more stringent developments in business life, the more difficult it is for any company to maintain customer satisfaction from its competitors. For this reason, service quality is needed to retain consumers, not only service quality, price and promotion are also the most important things in retaining consumers. This study aims to identify the effect of service quality, price, and promotions significantly on customer satisfaction at Muliamart. The sample used was 100 respondents. The method used uses quantitative methods. The sampling technique used in this study was purposive sampling technique, namely sampling with certain criteria. The analysis model used is multiple linear regression analysis processed using SPSS 2022. The results of this study indicate that Service Quality has a partial effect (3.636 > 1.988), Service Price has a partial effect (2.427 > 1.988), and Service Promotion has a partial effect of (3.422 > 1.988) t-count > t-table on Satisfaction. Meanwhile, service quality, price, and promotion have a simultaneous effect of (46,765 > 2,700) f-count > f-table on consumer satisfaction. the magnitude of the coefficient of determination (R Square) is 0.594 or equal to 59.4%. And the rest is influenced by other variables.